2013
DOI: 10.1364/oe.21.000764
|View full text |Cite
|
Sign up to set email alerts
|

Improved light extraction in the bioluminescent lantern of a Photuris firefly (Lampyridae)

Abstract: Abstract:A common problem of light sources emitting from an homogeneous high-refractive index medium into air is the loss of photons by total internal reflection. Bioluminescent organisms, as well as artificial devices, have to face this problem. It is expected that life, with its mechanisms for evolution, would have selected appropriate optical structures to get around this problem, at least partially. The morphology of the lantern of a specific firefly in the genus Photuris has been examined. The optical pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
(19 reference statements)
0
22
0
1
Order By: Relevance
“…[351] The light source (the reaction center) is contained inside a high-refractive-index medium, imposing boundary constraints on the morphology of the lantern in order to optimize light extraction to the outside air due to total internal reflection at large incidence angles. [352,353] Bay et al have recently shown that the structure of the cuticle outside of the light-emitting organ increases the efficiency of the light emission by ≈10%. [352] The light-extraction efficiency of synthetic electroluminescent devices, e.g., organic light-emitting diodes (OLEDs), suffers from the same refractive-index-mismatch, [354] and the insight from the firefly lantern structure has been used to improve light-extraction from OLEDs by up to 55%.…”
Section: Bioluminescencementioning
confidence: 99%
See 1 more Smart Citation
“…[351] The light source (the reaction center) is contained inside a high-refractive-index medium, imposing boundary constraints on the morphology of the lantern in order to optimize light extraction to the outside air due to total internal reflection at large incidence angles. [352,353] Bay et al have recently shown that the structure of the cuticle outside of the light-emitting organ increases the efficiency of the light emission by ≈10%. [352] The light-extraction efficiency of synthetic electroluminescent devices, e.g., organic light-emitting diodes (OLEDs), suffers from the same refractive-index-mismatch, [354] and the insight from the firefly lantern structure has been used to improve light-extraction from OLEDs by up to 55%.…”
Section: Bioluminescencementioning
confidence: 99%
“…[352,353] Bay et al have recently shown that the structure of the cuticle outside of the light-emitting organ increases the efficiency of the light emission by ≈10%. [352] The light-extraction efficiency of synthetic electroluminescent devices, e.g., organic light-emitting diodes (OLEDs), suffers from the same refractive-index-mismatch, [354] and the insight from the firefly lantern structure has been used to improve light-extraction from OLEDs by up to 55%. [353] …”
Section: Bioluminescencementioning
confidence: 99%
“…The bioluminescence of these tropical species of fireflies has been modeled in order to design and engineer next-generation LED lights which are orders of magnitude more energy-efficient [30,31]. However, the embodied energy underwriting the lighting system of each e-bike battery in the installation would require generating 500 hours of pedaling at 75 watts per hour just to generate the equivalent amount of energy used to make each battery [32].…”
Section: Isea Bright Futurementioning
confidence: 99%
“…The second pattern was fabricated based on Refs. 18,19 using electron beam lithography and silicon wet etching. From both of the patterns a nickel plate was made using electroplating.…”
Section: Fabricationmentioning
confidence: 99%